FACTORS DECISION TO VISIT A MOSQUE JAMI’ AIR TIRIS KAMPAR REGENT RIAU PROVINCE - Riska Novita Basuki; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This study aims to deter mine how the decision making factors and tourist send before coming to visit anattractione specially Mosque Jami' Air Tiris Kampar Regent Riau province.This study uses quantitative methods with descriptive approachtoexamine the issue in the lift. The samplein this study as many as 95 people were taken by using accidental sampling. While data collection techniques in this study using observation, questioner, andinter views. By using a Likert scaleas a measure to determine the length of the short interval.Based on the research that has been done, the public response to the decisionto visit the Mosque Jami' Air Tiris, as well asattracted by the uniquearchitecture of the building and the my thof the pool that contain srocks haped buffalo head.Keywords: Factors tourist decision, Mosque Jami’ Air Tiris, Kampar Regent